The Sedekah Bumi Tradition as an Effort to Improve Local Wisdom Education for Generations of the Nation - Merina Merina*; Lelly Qodariah; Cahya Adhitya Pratama (Riwayat: Educational Journal of History and Humanities, 2023)
The implementation of earth alms is a culture that is carried out from generation to generation by the people of Indonesia, especially on the island of Java as a form of gratitude for the gift of the earth's produce by God. The purpose of this study is to describe and analyze the earth alms tradition associated with character education in the form of moral values contained in the implementation of the tradition. This study uses a descriptive qualitative method with a literature study approach. The findings and results of this study indicate that culture is a strong solution to the demoralization that occurs in the nation's generation. This is stated in the values contained in the implementation of the earth alms tradition which includes social, religious, economic and other aspects.